Study of antibiotic resistance formation in gram-negative bacteria isolated from battle wounds - Kutasevych, Yanina; Dzhoraіeva, Svetlana; Khoroshun, Eduard; Honcharenko , Valentina; Kondakova, Hanna; Nehoduiko, Volodymyr; Ivantsova , Olena; Oliinyk, Olha (Annals of Mechnikov's Institute, 2024)
The purpose of the work is to determine the spectrum of sensitivity to antibiotics of P. aeruginosa and K. pneumoniae, isolated from gunshot and mine-explosive combat wounds, with the study of the rate of development of resistance to antibiotics of the carbopenem group. Materials and methods. Clinical strains (K. pneumoniae - 23, P. aeruginosa - 12) were used for the study, which were isolated from the wounded who received combat injuries localized in the lower limbs and were treated in the military medical clinical center of Kharkiv. Microbiological studies were conducted on the laboratory of microbiology, immunology and molecular genetics of the State Establishment "Institute of Dermatology and Venereology of the National Academy of Medical Sciences of Ukraine" using generally accepted methods. The results. A high degree of resistance of the leading pathogens of combat wound infection - K. pneumoniae and P. aeruginosa to most groups of antibiotics was established. In particular, 83.3% of clinical strains of P. aeruginosa, 78.3% of K. pneumoniae were insensitive to meropenem, and about 70% of these strains were insensitive to the combination of meropenem/vaborbactam. Experimentally, the rapid dynamics of the formation of resistance to meropenem is shown. Conclusions. The leading factors of infectious complications of combat wounds, K. pneumoniae and P. aeruginosa are characterized by multiple resistance not only to widely used antibiotics, but also to new combinations of antibiotics and beta-lactamase inhibitors, including reserve antibiotics, which creates an extremely threatening situation. Determination of the dynamics of the formation of resistance to meropenem in clinical strains of K. pneumoniae and P. aeruginosa showed a fairly rapid jump-like dynamics of the acquisition of resistance, which indicates the possibility of phenotypic realization of the genetically determined trait of resistance to carbapenems.